Focus sur les déclencheurs de l’évolution des actions d’accompagnement pédagogique - Mireille Houart; Dorothée Baillet; Bernard Cobut; Céline Vanden Eynde; Dominique Duchâteau; Sabine Goemaere; Anne-France Lanotte; Laurence Oger; Jim Plumat; Marie-Christine Pollet; Pauline Slosse; Didier Salmon (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Innovation most frequently begins with an institutional policy, requests from teachers and students, reports on dysfunctional settings or just simply through by wanting to change routines. Designing new educational measures needs to take into account several aspects of the environment. It is also influenced by the tutor’s status, his career and experience and can be supported by recent research in various fields and through exchanges of best practices between colleagues. Last of all, implementing such measures naturally leads to a cyclical framework based on assessment and regulation, shedding a new light on the original triggers of the innovation making readjustments possible. This three-step innovation process is described and illustrated through three actions that have been implemented in different teaching contexts in the Communauté française de Belgique.